Aspectos socioeconômicos e de (não)escolaridade dos moradores do Paredão e da Costa Bica (Piratini, RS) - Silva, Darlene Rosa da (2010)
This study is a qualitative and quantitative investigation. It has the aim to show the social and economic conditions, as well as the non-schooling, of people who live in Paredão and Costa do Bica (Piratini, RS). The study was developed in the months of January and February of the year 2008, when 114 families were visited, being 57 in Paredão and 57 in Cost do Bica. The main source of data consisted in structured interviews. From the interviews it was possible to collect data from 344 people. The responsible ones for the information were the 144 people who were available to answer the questions, as well as they could sign the authorization for public use of the collected data. The constant information from interviews which are shown in this study are about the social and economical conditions of the people who live in Paredão and Costa do Bica, and it is also about the non-schooling - the main focus of the dissertation. According to the non-schooling data of the people who live in Paredão and Costa do Bica, four basic points were revealed: the ones who were not in school age; the ones who were already enrolled in the City and the State Public Schools; the ones who were not at school anymore; and ones who have never been to school. The analisys that focus mainly the ones who are more than fifteen years old, are based on Ferraro Ferraro (1999; 2002; 2004), Galvão (2007), Pinto (2000), Ribeiro (1997; 2004; 2006), theories, besides others. The collected data from the structured interviews reveal that among people who are 15 or more, 40% are illiterate. The analisys indicated that illiteracy, in the mentioned areas, is related to social, historical and educational factors. Besides illiteracy, it was noticed, among other aspects, that children in obligatory school age do attend teaching public institutions, however those ones who are more than fourteen years old, and out of the obligation to attend school, experience school exclusion processes, since the schools do not provide the students who come from rural areas, with oportunities for being kept at school.